Strategi Digital Tourism dalam Meningkatkan Kunjungan Wisatwan di Desa Hendrosari Kapubaten Gresik - Heri Cahyo Bagus Setiawan; Aries Kurniawan; Beni Dwi Komara (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2022)
Hendrosari Village has an extraordinary function for health because it can treat various diseases, including: Kidney stone pain, Urinary tract pain, Back/waist pain due to being too tired/irregular in consuming drinking water. This is when viewed from the historical side of Hendrosari Village. Economically, judging from several studies and articles written by Setiawan, (2020), Komara (2020) and Kurniawan (2020), there is an explanation as follows: that this village has succeeded in developing the village into a palm tree-based tourism village. When the tourism sector is developed in Hendrosari village, of course it will create new economic channels from the village community. The MSME-based business sector has emerged with various types of products ranging from traditional processed products to modern ones (attractive packaging). This is then referred to as a blessing from the presence of the tourist village. This is in line with Setiawan's research (2020) that the tourism sector is a sector that influences each other economically and can synergize with each other if managed properly. However, based on our observations and in-depth observations, there are some interesting things to do research with the big questions are: How is digital tourism developed in Hendrosasi Village as an effort to increase the number of visitors? The research method used is a qualitative approach with three (3) resource persons to answer in the context of marketing and tourism promotion, namely how to increase the number of visitors using a digital system or in academic language called digital tourism.